2016
DOI: 10.1615/jenvironpatholtoxicoloncol.2016015298
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Alleviates Cadmium-Induced Damage and Overexpression of Epidermal Growth Factor Receptor and its Downstream Signaling Proteins in the Reproductive System of Male Swiss Albino Mice

Abstract: Nowadays, exposure to heavy metals and their detrimental effects in humans are grave health concerns. In this study, we investigated the protective effect of resveratrol (RES) against CdCl2 (cadmium chloride)-induced impairment of spermatogenesis, histopathological alterations, and the up-regulation of epidermal growth factor receptor (EGFR) signaling cascade in Swiss albino mice. Two different doses of CdCl2 were injected intraperitoneally into two groups of mice, and in the third group RES was administered o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…In particular, Re showed a protective action against testicular toxicity as it upregulated Bcl2, downregulated p53 and Bax gene expression [ 20 , 54 ], and reduced inflammatory cascade [ 54 ]. Furthermore, marked improvements in sperm parameters and histopathological damages were observed in the Re-pretreated mice [ 34 ]. Indeed, our study confirmed the positive role of Re in Cd-challenged animals on both biochemical and structural parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Re showed a protective action against testicular toxicity as it upregulated Bcl2, downregulated p53 and Bax gene expression [ 20 , 54 ], and reduced inflammatory cascade [ 54 ]. Furthermore, marked improvements in sperm parameters and histopathological damages were observed in the Re-pretreated mice [ 34 ]. Indeed, our study confirmed the positive role of Re in Cd-challenged animals on both biochemical and structural parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, resveratrol (Re), a polyphenol present in many plants and especially in red wine, showed antioxidant properties [ 30 ] as well a positive regulation of apoptosis and other zonula occludens protein expression, such as occludin [ 31 , 32 ]. In the testis, Re protected from oxidative stress [ 33 ], partially reversed the dysregulation of the apoptotic pathways [ 20 ], and improved sperm parameters and histopathological damage [ 34 ]. Recently, bergamot juice (BJ), obtained from the endocarp of Citrus bergamia Risso et Poiteau (bergamot) fruits, gained the attention of pharmaceutical companies interested in natural products and antioxidant bioactive compounds from dietary sources [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol‐mediated reversal of Cd‐induced testicular damage has been observed in rats, where administration of resveratrol (20 mg/kg bw) before or after Cd improved semen parameters, enhanced the concentration of serum gonadotropins, and reduced the lipid peroxidation in the testis (Eleawa et al, 2014). Pretreatment with resveratrol (10 mg/kg bw) significantly improved the various parameters of sperm, histological damage, as well as downregulation of the epidermal growth factor receptor signaling cascade in mice testis (Mitra et al, 2016). The ameliorative effect of grape seed extract (GSE), a powerful antioxidant containing high levels of vitamins C and E, was evaluated against CdCl 2 ‐induced dysfunctioning in rat testis.…”
Section: Remedies For the Management Of Cadmium‐induced Testicular Tomentioning
confidence: 99%
“…[ 36 ]. In vivo experiments showed that RSV also protected against Cd-induced perturbations of spermatogenesis and histology in mice [ 37 ].…”
Section: The Protective Effect Of Resveratrol On Oxidative Cell Stmentioning
confidence: 99%